Pengaruh Live Streaming Shopping Pada Aplikasi Tiktok Terhadap Minat Beli Skintific - Riza Hersiwi Nugraheni; Murwanto Sigit (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to analyze the effect of demand, comfort, interactivity and fun on the enjoyment felt by live streaming shopping viewers, as well as examine the impact of perceived pleasure on impulsive purchases of Skintific skincare. This study will use quantitative methods, purposive sampling techniques, and data analysis techniques using Structural Equation Modeling and then processed with the SmartPLS program. The results of the research from 162 respondents who are Tiktok live streaming shopping viewers and Skintific skincare users show that interactivity and cheerfulness have a positive effect on perceived pleasure, perceived pleasure has a positive effect on impulsive purchases. Meanwhile, demand and comfort do not have a positive effect on perceived enjoyment due to differences in the culture of the research location.